Oxidative stress biomarkers and otoacoustic emissions in humans exposed to styrene and noise. - Sisto, R.; Botti, T.; Cerini, L.; Sanjust, F.; Tranfo, G.; Bonanni, R.C.; Paci, E.; Pigini, D.; Moleti, A. (International Journal of Audiology, 2016)
Objective: Evaluating the correlation between otoacoustic emission levels, styrene exposure, and oxidative stress biomarkers concentration in styrene-exposed subjects, to investigate the role of oxidative stress in outer hair cell damage. Design: Distortion product otoacoustic emissions were measured in the exposed workers and in a control group. Separation between the distortion and reflection otoacoustic components was performed by time-frequency-domain filtering. The urinary concentration of the DNA and RNA oxidation products, namely 8-oxo-7,8-dihydroguanine (oxoGua), 8-oxo-7,8-dihydro-2′-deoxyguanosine (oxodGuo), and 8-oxo-7,8-dihydroguanosine (oxoGuo), were evaluated. Study sample: Nine subjects exposed to styrene in a fiberglass factory, eight control subjects. The two groups were statistically equivalent in mean age. Results: Statistically significant differences were found in the distortion component levels between the exposed and the control group. High levels of the oxidative damage biomarkers were found in the workers exposed to high levels of styrene. Significant negative correlation was found between the otoacoustic emission distortion component levels and the concentration of the oxoGuo biomarker. Conclusions: Exposure-induced damage of the cochlear amplifier is shown in the mid-frequency range, confirming animal experiments, in which hair cells in the cochlear middle turn were damaged. Hearing damage is consistent with the outer hair cell apoptosis pathway associated with oxidative stress.